Acid ceramidase expression reduces IFNγ secretion by mouse CD4+ T cells and is crucial for maintaining B-cell numbers in mice - Mandasari, Putri; Hollmann, Claudia; Zaidi, Rehan-Haider; Löw, Samira; Schrama, Jann; Wigger, Dominik; Schumacher, Fabian; Kleuser, Burkhard; Beyersdorf, Niklas (Frontiers in Immunology, 2024)
Acid ceramidase (Ac) is a lysosomal enzyme catalyzing the generation of sphingosine from ceramide and Ac inhibitors are currently being investigated as potential cancer therapeutics.Yet, the role of the Ac in immune responses, particularly anti-viral immunity, is not fully understood. To investigate the impact of Ac expression on various leukocyte populations, we generated a tamoxifen-inducible global knock-out mouse model for the Ac (iAc-KO). Following tamoxifen administration to healthy mice, we extracted primary and secondary lymphoid organs from iAc-KO and wild-type (wt) littermates and subsequently performed extensive flow cytometric marker analysis. In addition, we isolated CD4 + T cells from the spleen and lymph nodes for sphingolipid profiling and restimulated them in vitro with Dynabeads TM Mouse T-Activator CD3/CD28. Intracellular cytokine expression (FACS staining) was analyzed and secreted cytokines detected in supernatants. To study cell-intrinsic effects, we established an in vitro model for iAc-KO in isolated CD4 + T and B cells. For CD4 + T cells of iAc-KO versus wt mice we observed reduced Ac activity, an increased ceramide level and enhanced secretion of IFNg upon CD3/CD28 costimulation. Moreover, there was a marked reduction in B cell as well as plasma cell and blast numbers in iAc-KO compared to wt mice. To study cell-intrinsic effects and in line with the 3R principles we established in vitro cell culture systems for iAc-KO in isolated B and CD4 + T cells. Our findings pinpoint to a key role of the Ac in mature B and antibody-secreting cells as well as in IFNg secretion by CD4 + T cells.